Book Reviews. (1st August 2013) - ,
Abstract : BOOK REVIEWS Robert B. Marks, China: Its Environment and History (Wang Lihua) Sam White, The Climate of Rebellion in the Early Modern Ottoman Empire (Onur Inal) Mark Fiege, The Republic of Nature: An Environmental History of the United States (Lisa M. Brady) Diana K. Davis and Edmund Burke III (eds.), Environmental Imaginaries of the Middle East and North Africa (Stuart Schoenfeld) J. Keri Cronin, Manufacturing National Park Nature: Photography, Ecology, and the Wilderness Industry of Jasper (Jacqueline McIsaac) Tim Sands, Wildlife in Trust: a Hundred Years of Nature Conservation (John Sheail) Marianna Dudley, An Environmental History of the UK Defence Estate 1945 to the Present (T.C. Smout) Ray Hilborn, with Ulrike Hilborn, Overfishing: What Everyone Needs to Know and Mansel G. Blackford, Making Seafood Sustainable: American Experiences in Global Perspective (Joseph E. Taylor III)